Density Functional Theory-Based Study of CO2 Vibrational Frequencies in Dimer Ionic Liquids (Journal of Scientific Research, 2025)
The vibrational frequency analysis of ionic liquids (ILs) interacting with CO₂ represents a rapidly emerging field, yet significant gaps persist in understanding microscopic interactions at the molecular level, particularly regarding solvation dynamics and structural relaxation. In this study, density functional theory (DFT) was employed to optimize the structures of the cation, anion, and cation–anion ion pairs of 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMImBF₄]), focusing on stable geometries. The structural properties and vibrational frequencies of the [EMImBF₄]₂ dimer were systematically investigated, followed by an analysis of the [EMImBF₄]₂-CO₂ complex. Scaled vibrational frequencies were compared with experimental far-infrared and Raman spectra, revealing critical insights into the ν₃ asymmetric stretching mode of CO₂. The dimer model demonstrated superior accuracy in representing CO₂ interactions compared to monomeric systems, with energy differences of 2.8 kcal·mol⁻¹ observed in the liquid phase. These findings enhance the understanding of CO₂ behavior in IL environments, offering implications for CO₂ capture technologies and spectroscopic interpretation.